Sensorless Control of Brushless Doubly-Fed Generator Using Luenberger Observer Based Wind Energy Conversion Systems - Hicham Serhoud; Djilani Benattous (Institute of Advanced Engineering and Science, 2018)
This paper investigates the use of Luenberger observer for sensorless power control of brushless double fed induction machine (BDFM) in wind energy conversion systems, the control strategy for flexible power flow control is developed by applying flux oriented vector control (technique), In order to estimate the rotor speed, an adaptive algorithm based on Lyapunov stability theory will be design. Finally the analyzed and simulation results in MATLAB/ Simulink platform confirmed the good dynamic performance of this new sensorless control for BDFG based variable speed wind turbines.